Protocol for a qualitative study exploring haemodialysis dependent patients’ arteriovenous fistula experience, values and concerns in Sydney, Australia - Vasi Naganathan; Sarah Joy Aitken; Bethany Miriam Stavert; Susan Monaro; Lisa Tienstra (BMJ Open)
Introduction The experiences of patients from culturally and linguistically diverse backgrounds, with chronic mental illness, disabilities or who identify as sexual or religious minorities are under-represented in clinical research on arteriovenous fistula (AVF) for haemodialysis access. A greater understanding of the experiences, values and concerns of these diverse patient groups are needed to provide haemodialysis access care that addresses the needs of all haemodialysis-dependent patients. This study seeks to describe a broad range of patient experiences related to the creation, care and surveillance of AVFs, including interactions with healthcare teams.Methods and analysis This qualitative study will use semistructured interviews with individual patients purposefully selected to provide a diverse patient population. A deliberate strategy will be used to recruit a demographically broad range of participants. Thematic analysis of interview transcripts, using a constant comparative methodology, will generate themes that describe patient experiences, values and concerns. Findings from this study will give a nuanced insight into the experiences of patients on haemodialysis with respect to their AVF.Ethics and dissemination Ethical approval for this study was provided by the Sydney Local Health District Human Research Ethics Committee (REGIS identifier: 2021/ETH00362, CH reference number: CH62/6/2021-033). Results will be made available to the participants, local health district, funders and other researchers through various hospital and academic forums. Data will also be published in peer-reviewed journals and be part of a larger body of work looking into patient-reported outcome measures for patients with AVF.